Інтегральні зображення розв'язків нестаціонарних задач теплопровідності для багатошарових циліндричних півпросторів - Конет, І.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The exact analytical solution of the nonstationary heat problem for many-layer cylindrical half-spaces is constructed by the method of integral transformations.